Evaluation of complication rates and vertical bone gain after guided bone regeneration with non‐resorbable membranes versus titanium meshes and resorbable membranes. A randomized clinical trial. (26th July 2017) - Cucchi, Alessandro; Vignudelli, Elisabetta; Napolitano, Aldo; Marchetti, Claudio; Corinaldesi, Giuseppe
Abstract: Background: The partial edentulous posterior mandible is often a challenge area that requires a bone reconstructive surgery for implants placement. Purpose: This RCT was aimed to evaluate complications rate and vertical bone gain after Guided Bone Regeneration (GBR) with dense non‐resorbable d‐PTFE titanium‐reinforced membranes (Group A) versus titanium meshes covered by cross‐linked collagen membranes (Group B). Material and Methods: 40 partially edentulous patients with atrophic posterior mandible, were randomly divided into two study group: 20 patients were treated with one stage GBR by means of non‐resorbable d‐PTFE titanium‐reinforced membranes (Group A); and 20 patients, by means of titanium mesh covered by cross‐linked collagen membranes (Group B). All complications were recorded, distinguishing between "surgical" and "healing" and between "minor" or "major.". Primary implants stability and vertical bone gain were also evaluated. Results: In the group A, surgical and healing complication rates were 5.0% and 15.0%, respectively. In the group B, surgical and healing complication rates were 15.8% and 21.1%, respectively. No significant differences between two study group were observed regarding complications rate implant stability and vertical bone gain. Conclusions: Both GBR approaches for the restoration of atrophic posterior mandible achieved similar results regarding complications, vertical bone gain and implant stability.